(3JSgjd GdefGaY aj GdWH hGdMceI GdeTJed Ydi (B"(3TaGA GdCLSGe hcJGH GdQMeI(B"s - (3EHQGgje Hf YHO GdQMef Hf Ydj Hf GHi HcQ GdCRQas ((3CMeO Hf Ydi Hf eMeO GdLdGdi s)
(3ChdgG (B:s
(3GeG HYO (B: (3aEf GdWH Yde YXje faYg adeG QCjJ GdeYJfi Hg bdjdG afTWfi Pdc Edi LeY TF ef gPG Gdaf ,ahLOJ GdMceGA bO hVYhG ajg caGjI eeG CdahG , cGf TaGA GdCLSGe dTjNfG GdceQGfi s
(3BNQgG (B:s
(3gPG GdZdGe ,hgPg GdCeI , hgPg GdOGHI CVjb ef LdO Led hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B172 - (3U(B309s
(3GdfSNI HgG MhGTs
(3GfXQ agQS GdWH HQbe (B47 " (3JMaI GdeLH ai UfGYI GdbdH (B"s
(3YdjgG JbjjOGJ cKjQIs
(3hhQbI GdNWHI eYGOI dGVWQGHgG hENJdGWgG HhQbI ef GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdWHs